2008
DOI: 10.1093/ndt/gfn354
|View full text |Cite
|
Sign up to set email alerts
|

Renal vasculitis in Japan and the UK--are there differences in epidemiology and clinical phenotype?

Abstract: We identified 27 cases of renal vasculitis (Wegener's granulomatosis 13, microscopic polyangiitis 11, Churg Strauss syndrome 3) fulfilling the case definition. The overall average age was 63.5 years which is less than those of the Japanese patients. The overall annual incidence of renal vasculitis was 12.2/million similar to Japan. The annual incidence of Wegener's granulomatosis was 5.8/million, microscopic polyangiitis 4.9/million and Churg Strauss syndrome 1.4/million. ENT and neurological involvement were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 9 publications
6
64
1
4
Order By: Relevance
“…The geographical studies of AAV indicated the predominance of MPA and MPO-ANCA positivity as epidemiologically specific to Japan, whereas GPA and PR3-ANCA positivities are dominant in European countries. 9,[17][18][19] According to the results in the present study, this Japanese specificity is consistent with the epidemiology of patients without HP; however, the epidemiology of patients with HP is similar to that of patients in European countries. With regard to the pattern of ANCA positivity, frequency of PR3-ANCA was equal to that of MPO-ANCA in patients with HP, although the predominance of MPO-ANCA has been demonstrated in the Japanese population with GPA.…”
Section: Discussionsupporting
confidence: 88%
“…The geographical studies of AAV indicated the predominance of MPA and MPO-ANCA positivity as epidemiologically specific to Japan, whereas GPA and PR3-ANCA positivities are dominant in European countries. 9,[17][18][19] According to the results in the present study, this Japanese specificity is consistent with the epidemiology of patients without HP; however, the epidemiology of patients with HP is similar to that of patients in European countries. With regard to the pattern of ANCA positivity, frequency of PR3-ANCA was equal to that of MPO-ANCA in patients with HP, although the predominance of MPO-ANCA has been demonstrated in the Japanese population with GPA.…”
Section: Discussionsupporting
confidence: 88%
“…Three other studies did give rise to some concerns: the study from Lithuania (33) was hospital based and may have missed community cases, the diagnostic criteria used by Zeft et al (34) were not stated in their abstract, and the study from Japan (35) was based on referral to a renal unit and may have missed those with nonrenal disease. However, the denominator population in this case was clearly defined (35), and other sources (36) attest to the rarity of WG in this region. We extracted the number of cases of each disease entity, noting the location, year of publication, and the source population, e.g., general, adult-only.…”
Section: Methodsmentioning
confidence: 65%
“…Apart from that there are no convincing data that the incidence of AAV varies among different countries except what can be explained by age differences. However, antigen specificity and disease phenotype do vary between populations (19). Figures from England, Japan and Sweden indicate the incidence of ANCA associated nephritis (AAN) to be 15 per million (16,19).…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…However, antigen specificity and disease phenotype do vary between populations (19). Figures from England, Japan and Sweden indicate the incidence of ANCA associated nephritis (AAN) to be 15 per million (16,19).…”
Section: Scope Of the Problemmentioning
confidence: 99%